Acceptance and net benefits of continuous audit in the public administration - Freitas, Marcelo Machado de (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Sócio-Econômico, Programa de Pós-Graduação em Contabilidade, Florianópolis, 2022.